Penafsiran M. Hasbi Ash-Shiddieqi terhadap Ayat-Ayat Hukum dalam Tafsir An-Nur (UINSI Samarinda, 2014)
This study is intended to reveal the interpretation M. Hasbi Ash-Shiddieqi to verses of law. Verses of law examined in this study is the verse about the law cutting off hands, adultery and veil. The method used is descriptive analysis. The main reference source used as research material is Tafsir al-Majid al-Nour Qur'anul by M. Hasbi Ash-Shiddieqy. Research describes, interpretation Hasbi Ash-Shiddieqi using bi-ra'yi interpretation. The method used is the method that is detailed tahlili interpret verse by verse in accordance with the order of verses and Surah contained in the Manuscripts by discussing various aspects. In terms of style, Hasbi tend to use shades of interpretation bi al-Ma'sur. This can be proved by looking at the general characteristics of methods such as: interpreting the verse by verse, interpreting the verses of the Koran with tradition and interpret the verses of the Koran with sahabat or tabi'in opinion.